Towards effective implementation of gender-based violence policies in Mankweng Township - Matshidiso Caroline Ngwepe; Xolani Thusi; Martinus M. Selepe (Insights into Regional Development)
Gender-Based Violence (GBV) remains a pervasive and complex issue in South Africa, particularly affecting women and girls. This study delves into the heart of this problem by focusing on Mankweng Township, an area marked by diverse cultural influences and socioeconomic challenges. Drawing upon a combination of interviews, questionnaires, and focus group discussions, this research comprehensively examines GBV, its root causes, and the experiences of its victims and survivors. The findings illuminate a nuanced picture of GBV, transcending conventional narratives. While the study confirms the predominant role of men as perpetrators, it also recognises that not all men adhere to violent behaviours. Men, women, and members of the LGBTQ+ community in Mankweng Township face varying degrees of violence and discrimination, thus challenging stereotypical perceptions. Traditional customs and cultural norms are revealed as powerful factors perpetuating GBV. The practice of lobola, emphasising ownership of women, and the subjugation of women in relationships are particularly highlighted. However, the study also uncovers potential solutions within cultural and religious frameworks where churches can serve as safe spaces for dialogue and support. Importantly, the research spotlights the often-overlooked experiences of the LGBTQ+ community, who face a disproportionately high risk of GBV. The fear of judgment and discrimination stifles their ability to seek help and report incidents. This underscores the need for a more inclusive approach to GBV prevention and intervention programs. The study's recommendations highlight the importance of awareness programs, better resource distribution, and cultural re-evaluation. It emphasizes the need to involve men and boys actively in GBV prevention efforts, challenging harmful gender norms and behaviours. As explored in this study, the legislative framework provides a robust foundation for addressing GBV. However, the study also highlights the critical importance of effective implementation and enforcement of these laws.